An atypical case of Klippel-Trénaunay syndrome presenting with crossed-bilateral limb hypertrophy and postaxial polydactyly: a case report - Rawan M. Al-Najjar; Rafael Fonseca (BMC, 2019)
Abstract Background Klippel-Trénaunay syndrome (KTS) is a rare congenital condition characterized by the clinical triad of capillary malformations (port wine stains), varicose veins with or without venous malformations, and bony and/or soft tissue hypertrophy. Case presentation Here we report the first case of a one-day-old male with KTS presenting with crossed-bilateral limb hypertrophy and post-axial polydactyly. Conclusion This case serves to highlight the variable presentation and multiple problems faced by patients with KTS and why multidisciplinary management is mandatory.